Existentialist perspective of literacy promotional campaigns (2018)
Advances have been made in the formal educational system with the incursion of the private sector. Despite this progress, adult literacy which is driven mostly by the non-formal sector still needs more promotional efforts by individuals and groups instead of relying on government efforts and development partner activities. This paper argues that to start from the premise that everybody knows is not only a fallacy but also an undermining factor for all literacy promotional campaigns